Rosai-Dorfman-Destombes disease: case series and literature review. - Richter Cicogna, Júlia Isabel (2022)
Rosai-Dorfman-Destombes disease (RDD) is a rare histiocytic disorder with a prevalence of 1:200 000 people in the United States.  The characteristic clinical presentation is a large and painful bilateral cervical mass in young adults, but more than a quarter of cases show extranodal manifestations.  Skin, paranasal sinuses, soft tissue, bone, salivary glands, oral cavity, and central nervous system can be affected, resulting in a very distinct constellation of symptoms in each patient. Systemic manifestations such as fever and leukocytosis are also frequent. The usual course is benign, with spontaneous regression in many cases. However, a minority of patients suffer from a progressive disease, occasionally resulting in death, usually due to local infiltration of vital structures.  This study aims to describe the clinical, radiologic, and anatomopathological characteristics as well as individualized therapeutic procedures and outcomes of five cases of RDD disease that have been diagnosed in a reference hospital in São Paulo and compare these findings with recent bibliography on this rare disease.